A new design concept: 3D to 2D textile pattern design for garments. (August 2017) - Lu, Shufang; Mok, P.Y.; Jin, Xiaogang
Abstract: ' The word "fashion" is synonymous with the word "change". Fashion begins with fabrics and fabrics begin with colour' . This famous remark/definition of 'fashion' must now be revised in the era of digital technology. In this paper, we propose a novel print design concept, from 3D garments to 2D textiles. By taking advantage of the cutting-edge developments in surface parameterisation, cloth simulation and texture assignment, we develop a computer system that allows designers to create figure-flattering prints directly onto 3D garments, and will output 2D pattern pieces with matched texture that are ready for digital printing and garment production. It reverses the traditional design process from 2D fabrics to 3D garments. The results produced by the proposed method guarantee textural continuity in both garment and pattern pieces. It not only releases apparel makers from the tedious work of matching texture along seams, but also provides users with a new tool to create one-of-a-kind fashion products by designing personalised prints. Highlights: A computer system reversing the textile and fashion design process is proposed. Creating prints directly on 3D garments and obtaining 2D pattern pieces with matched prints for later garment production. Creating fashion products with figure-flattering prints for individual customers. Unbroken continuity of design eliminates tedious pattern placement. Low-distortion surface parameterisation occurs between 3D garment and 2D patterns.